Unmet clinical needs in women with aesthetic manifestations of polycystic ovary syndrome: a cross-sectional study - Estermann, Julia; Bitterlich, Norman; Weidlinger, Susanna; Bachmann, Annette; Sourouni, Marina; Stute, Petra (Journal of women's health, 2023)
Background: Polycystic ovary syndrome (PCOS) management has hardly been standardized until recent years. There is an accurate, evidence-based guideline published by the European Society of Human Reproduction and Embryology (ESHRE). However, it remains unclear to which extent, if at all, the guideline is followed by health care providers. The aim was to explore the subjectively perceived quality of gynecological medical care in women with PCOS suffering from aesthetic complaints. - Materials and Methods: A nonvalidated questionnaire was constructed in a standardized manner covering the domains: aesthetic aspects, metabolism, menstrual cycle, reproduction, mental health, and prevention of chronic noncommunicable diseases. - Results: A total of 1960 participants with aesthetic complaints, such as acne (66.2%), alopecia (43.9%), hirsutism (77.9%), or overweight/obesity (72.3%) were included. The percentage of women being counseled was low (acne 20.3%, alopecia 12.9%, hirsutism 17.5%, overweight/obesity 36.2%). Satisfaction with counseling was moderate (40.4-44.1 points). Many women tried at least one therapeutic method (75.9%), whereas only a few were counseled for therapy (acne 27.0%, alopecia 24.6%, hirsutism 24.0%, overweight/obesity 18.8%) with moderate satisfaction for hyperandrogenism (mean 55.1-59.5 points) and good satisfaction for overweight/obesity (mean 60.8 points). Overall satisfaction was rated with a mean of 30.5 points (standard deviation 27.1) on a scale from 0 to 100 and thus considered “not satisfied.” Fewer complaints were significantly correlated with higher satisfaction. Most women wished for more counseling (80.8%), as well as more diagnostic (63.2%) and therapeutic options (70.2%). - Conclusions: Women affected by PCOS are not properly managed according to the ESHRE guideline. Indeed, this guideline recommends comprehensive history and physical examination for clinical hyperandrogenism as well as holistic approaches in therapy, including education and counseling of patients. Still, overall consultation rates and satisfaction were poor.
Gesehen am 31.05.2024